Media Relations and Minority Groups an A Sociological Regulation (Wahabi's Existence in Indonesia) - Hasan Sazali; Idawati Idawati; Hota Sari (International Journal of Social Service and Research (IJSSR), 2023)
In the context of the right to religious freedom. Minority groups have not received serious attention from the upper class, this is evident in the many minority rights that must be fought for. Minority groups are often overlooked or underrepresented in the media, most minority groups play less of a role in television programs. Minority groups are often misinterpreted through prejudices held by the majority. The position of the Indonesian mass media as a social institution in relation to society is very important, where the position of the media has a very power that can be considered to make a better living society. The  wahabi movement is sometimes also associated with salafist groups referring to salafist clerics (earlier Ulama), Wahabi or Salafi marking the movement of Islamic conservatism. This movement is associated by some circles with various radical movements, considering that its approach is often to fictionalize or silence others, so the term Wahabi as a pejorative form, a term that contains negative meanings. The study aims to find out relations of media and minority groups to the existence of Wahhabism in Indonesia. Library research method is used in this study. From the findings in this article which uses a literature study, the relationship between media and minority groups in the existence of Wahabi, it can be seen that the media has experienced media success in partiality towards minority groups. Wahabi who feel part of a minority group, by building and establishing relationships with the media, succeed in bringing about new changes, through the media, their guidance as a minority group their rights are successfully fulfilled.